Increased microcirculation detected by dynamic contrast‐enhanced magnetic resonance imaging is of prognostic significance in asymptomatic myeloma. (15th March 2016) - Hillengass, Jens; Ritsch, Judith; Merz, Maximilian; Wagner, Barbara; Kunz, Christina; Hielscher, Thomas; Laue, Hendrik; Bäuerle, Tobias; Zechmann, Christian M.; Ho, Anthony D.; Schlemmer, Heinz‐Peter; Goldschmidt, Hartmut; et al.
Summary: This prospective study aimed to investigate the prognostic significance of dynamic contrast enhanced magnetic resonance imaging (DCE‐MRI) as a non‐invasive imaging technique delivering the quantitative parameters amplitude A (reflecting blood volume) and exchange rate constant kep (reflecting vascular permeability) in patients with asymptomatic monoclonal plasma cell diseases. We analysed DCE‐MRI parameters in 33 healthy controls and 148 patients with monoclonal gammopathy of undetermined significance (MGUS) or smouldering multiple myeloma (SMM) according to the 2003 IMWG guidelines. All individuals underwent standardized DCE‐MRI of the lumbar spine. Regions of interest were drawn manually on T1‐weighted images encompassing the bone marrow of each of the 5 lumbar vertebrae sparing the vertebral vessel. Prognostic significance for median of amplitude A (univariate: P < 0·001, hazard ratio (HR) 2·42, multivariate P = 0·02, HR 2·7) and exchange rate constant kep (univariate P = 0·03, HR 1·92, multivariate P = 0·46, HR 1·5) for time to progression of 79 patients with SMM was found. Patients with amplitude A above the optimal cut‐off point of 0·89 arbitrary units had a 2‐year progression rate into symptomatic disease of 80%. In conclusion, DCE‐MRI parameters are of prognostic significance for time to progression in patients with SMM but not in individuals with MGUS.